Tertiary Uplift and the Miocene Evolution of the NW Borneo Shelf Margin - Franz L. Kessler; John Jong (Berita Sedimentologi, 2015)
NW Borneo, of which the shelfal margin extends from the West Baram Line in the southeast to the Balabac Line in the northwest, encompasses an area of active hydrocarbon exploration since the 1970’s. A large number of the earlier oil and gas finds are located in shelfal reservoirs of Neogene age. In this study, we portray the development of the Miocene shelf from the standpoints of stratigraphy, sea sea-level fluctuations, hinterland uplift and sediment recycling; mobile clay tectonics and, last but not least, the impact of the monsoon climate. Balancing the different viewpoints, we believe the transition from a muddy Mi Mid-Miocene shelf to an unusually sandy one can be attributed to two independent factors, which are:The rise of the Borneo part of Sundaland in the Middle to Late Miocene, caused by tectonic compression, in combination with the influence of the monsoon climate, andThe availability, through erosion of the Rajang/Crocker system, of massive amounts of sand delivered to the basin in geologically short time intervals.The Early to Mid-Miocene Cycle III/Stage III “Setap Shale” and other sediments in the Baram Delta appear characteristically lean in sand in most areas. The available data suggest that the first massive regional sand pulse originated at the same time in the Baram Delta, Brunei and Sabah, during Cycle IV/Stage IVA (Serravallian), post-MMU/DRU times. Continued sand supply established a shelf edge that remained almost stationary throughout Mid Cycle V/Stage IVC. As compression and uplift continued, the Middle to Late Miocene Cycles IV/V (Stages IVA-E) shelf saw local modification by hydraulic clay injection. During Cycles V/VI, and also in the Stages IVD-F, we see a further major expansion of the shelf. The question, as to which of these pulses can be linked to sea-level fluctuations, remains open; though it appears that the Borneo uplift has “outrun” rising sea-level at least since the Late Pleistocene.